2010
DOI: 10.3109/17435390903428851
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin contamination of engineered nanomaterials

Abstract: Endotoxin has established health impacts and may be a potential confounding factor in toxicity studies of engineered nanomaterials (ENM). We aimed to characterize endotoxin contamination for a representative set of carbon-based ENM. The established method for quantifying endotoxin relies on its activity in a complex biochemical assay system. Because of their physical and chemical properties, measurement of endotoxin associated with many ENM presents non-trivial technical challenges. We have made progress in id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Dispersions of nanoparticles were prepared in a standardized procedure as previously described (Schulze et al 2008). Moreover, each NP dispersion was tested to be free of lipopolysaccharides, that is, endotoxins that induce inflammatory responses or oxidative stress in cultured cells (Esch et al 2010;Schulze et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Dispersions of nanoparticles were prepared in a standardized procedure as previously described (Schulze et al 2008). Moreover, each NP dispersion was tested to be free of lipopolysaccharides, that is, endotoxins that induce inflammatory responses or oxidative stress in cultured cells (Esch et al 2010;Schulze et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was shown that activated carbon, a carbon allotrope, can adsorb endotoxins (Du et al, 1987). Recent studies have also tried to understand the interaction of endotoxins with CBNs (Esch et al, 2010;Jackson et al, 2015). However, the methodology of endotoxin detection used in the latter studies did not consider the fact that endotoxins can bind CBNs and, therefore, interfere with the LAL assay itself.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major concerns in NMs manufacturing is the sterility of the environment in which the material is being synthesized. Even though a large number of publications have addressed the issue of CBNs toxicity, very few have warned about the potential for contamination with endotoxins (Esch et al, 2010;Cha et al, 2013;Zhang et al, 2013;Amenta and Aschberger, 2015;Jackson et al, 2015). Endotoxins are also known as lipopolysaccharide (LPS), an endogenous pyrogen.…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of MRG-qPCR to nanotoxicologic research is critical due to the unpredictability of nanoparticle-gene interactions and the complex intracellular behavior of GNPs in situ . The concentration of endotoxin (Esch et al 2010) in our cultures was also evaluated to confirm that steroidogenic modulation was due to low-dose GNP exposure and not to this toxic confounder (Taylor and Terranova 1996). This evidence together with the lack of an oxidative-stress response in the present study suggests that the endotoxin present in our culture solutions did not contribute to the observed steroidogenic responses.…”
Section: Discussionmentioning
confidence: 99%